The SUS and the Triad of Urban Arboviruses (2015-2020): Essay about the Inevitable Correlation between Public Health and Society (Global Journal of Medical Research, 2021)
This essay analyzes the links between the Sistema #xDA;nico de Sa#xFA;de (SUS) and the different social scopes, from reflections about the presence of three arboviruses transmitted by Aedes Aegypti: Dengue, Chikungunya and Zika. This text is more social history approach than an analysis of specific biological and pathological aspects related to each of these diseases. The concepts of Space of Experience and Horizon of Expectation, as proposedby Reinhart Koselleck, are used to support the argument that defends the importance of SUS in recently and in the future. Furthermore, we also present the concept of Inevitable Correlation, proposed by us as essential to a theoretical-methodological approach concerned with investigating objects of historical problematization in a network perspective that fundamentally interconnects them. We start from the hypothesis that thinking about SUS, one of the main foundations of public health in Brazil, involves considering the network of people and institutions that coexist with it.
Keywords: SUS; inevitable correlation; urban arbovirus; public health; Brazil